Spor fotoğrafçılığı ve teknoloji ile etkileşimi - Say, İlker (My University, 2019)
Günümüz teknoloji çağında sporun birleştirici gücünün etkileri tartışılamaz. İnsanlık tarihiyle neredeyse eşit olan spor, başkaları tarafından da takip edilmesi açısından çok önemlidir. Bu takibin de Spor Muhabirleri ve Spor Fotoğrafçıları vasıtasıyla kitlelere ulaştırılması açısından bu tez hazırlanmıştır.İlk bölümde sporun ve spor fotoğrafçılığının tarihi hakkında bilgiler verilmiştir. İleriki bölümlerde spor fotoğrafçılığının kapsadığı alanlar, değişen ve gelişen teknolojinin spor fotoğrafçılığına etkileri ve kullanılan tekniklerden bahsedilmiştir. Son olarak da bu alanlarda çalışmalar yapan profesyonel spor fotoğrafçılarıyla birebir görüşmelerle tez sonuçlandırılmıştır.

In today's age of technology, the effects of sport's unifying power are unquestionable. Sport has an history which is almost equal to the history of humanity and it has a quite significant effect on people not only sportsmen who directly engaged in sports but also for those following sports competitions through various media. This thesis was prepared in order to explain the role of Sports Reporters and Sports Photographers for the follow-up of sports by the masses of people. In the first part of this thesis, there is a brief information about the history of sports and sports photography. In the following parts, the fields covered by sports photography, the effects of changing and developing technology on sports photography and the related techniques are discussed respectively. In the last part, the thesis completed with one on one interviews with professional sports photographers.
Keywords: Basın; Çekim Teknikleri Sports; Fine arts education; Fotoğrafçılık; Güzel sanatlar eğitimi; Photography; Press; Shooting Techniques; Spor; Spor Fotoğrafçılığı; Sports Photography; Technology; Teknoloji